Pharyngeal colonization with Haemophilus influenzae type b among healthy Turkish infants and children - KARAHASAN, AYŞEGÜL; ÜLGER, NURVER; İLKİ, ZEYNEP ARZU (My University, 2002)
BACKGROUND: An absence of Haemophilus influenzae type b (Hib) disease surveillance and epidemiological data on the pharyngeal carriage of Turkish children causes delay in the introduction of conjugated Hib vaccination into proposed national vaccination programs. METHODS: Oropharyngeal cultures were obtained from 1404 healthy infants and children. Six healthy child clinic (HCC), 11 day-care centers (DCC) and seven elementary schools (ES) were randomly selected in seven different counties at the Anatolian side of Istanbul between January and April 2000. RESULTS: Haemophilus influenzae was isolated from 315 (22.8%) of all participants and 98 (31%) isolates were serotype b. The carriage rate for Hib was higher in children at DCC (43 out of 448, 9.6%) and ES (46 out of 504, 9.1%) compared to infants 0-24 months of age (nine out of 430, 2.1%) presented to HCC. All Hib isolates were susceptible to azithromycin, chloramphenicol and cefotaxime. Beta-lactamase production was detected in only one isolate. Trimethoprim-sulfamethoxazole resistance was found in 8.5% of Hib isolates. Multivariate analysis showed that DCC and ES attendance were independent predictors of Hib carriage. CONCLUSION: A significant proportion of healthy Turkish children was shown to be colonized with Hib. The burden of invasive Hib infections should be determined in order to evaluate the Hib conjugated vaccine as a part of a routine immunization program in Turkey.
Keywords: Humans; Turkey; Infant; Child; Child, Preschool; Pharynx; Child Day Care Centers; Haemophilus influenzae type b